Vascular-Bed-Specific Hemostasis and Hypercoagulable States: Clinical Utility of Activation Peptide Assays in Predicting Thrombotic Events in Different Clinical Populations - Rosenberg, Robert D. (Thrombosis and Haemostasis, 2001)
This chapter summarizes the new paradigm for arterial thrombosis. This new paradigm emphasizes the heterogeneity of endothelial cells and the signaling pathways that control endothelial cell gene expression in surrounding tissue. It is suggested that genetic alterations in the signaling pathways are probably responsible for localized thrombosis, as manifested by heart attacks and strokes. A discussion of two clinical studies supporting the new arterial thrombosis paradigm is also included in this chapter. These studies, carried out by genetic engineering in mice, employ activation peptides to help predict the occurrence of thrombotic events in humans.
Keywords: Activation peptides; arterial thrombosis; vascular beds; tissue factor; hypercoagulability